CD44 deficiency represses neuroinflammation and rescues dopaminergic neurons in a mouse model of Parkinson's disease - Yuejun Wang; Li Li; Yuting Wu; Shouping Zhang; Qianqian Ju; Yinuo Yang; Yan Jin; Hui Shi; Cheng Sun (Elsevier, 2022)
CD44 is a transmembrane protein that transduces extracellular stimuli to immune response. Neuroinflammation is a causative factor in neurodegenerative diseases, such as Parkinson's disease (PD). Owing to its role in inflammation, this study investigated whether CD44 is involved in the pathological progression of PD. Our data showed that CD44 deficiency largely abolished proinflammatory cytokine expression in primary microglia and astrocytes. In PD model mice, CD44 knockout improved behavioral defects, prevented TH loss in the SNpc and striatum, and blocked activation of microglia and astrocytes. Moreover, CD44 neutralization by anti-CD44 antibody recapitulated the phenotypes observed in CD44 knockout mice. Mechanistically, CD44 neutralization blocked TLR4 expression and NF-κB p65 nuclear translocation induced by lipopolysaccharide in BV2 cells. Overall, our results indicate that CD44 deficiency has a beneficial role against PD, which is likely due to repression of the TLR4/NF-κB axis, leading to reduced neuroinflammation. Therefore, CD44 might be a therapeutic target for the development of anti-PD agents.